A study on offshore wind farm siting criteria using a novel interval-valued fuzzy-rough based Delphi method. (15th September 2020) - Deveci, Muhammet; Özcan, Ender; John, Robert; Covrig, Catalin-Felix; Pamucar, Dragan
Abstract: This study investigates the degree of importance of criteria affecting the optimal site selection of offshore wind farms. Firstly, forty two different influential criteria have been selected by reviewing the scientific literature on offshore wind farm site selection. Secondly, a survey has been conducted receiving a response from thirty four internationally renowned experts across seventeen countries. Each participant is asked to indicate the importance and relevance of each criterion based on their experience. Finally, the importance of each criterion for offshore wind farm site selection is determined using a novel Decision Making-Level Based Weight Assessment (LBWA) approach based on interval-valued fuzzy-rough numbers (IVFRN). The proposed method allows exploitation of the uncertainties and subjectivity that exist in the decision-making process. The results from this study improve our understanding of the importance and impact of each criterion which we believe would be invaluable for the future studies on the site selection of offshore wind farms. Highlights: Identify the importance of various criteria for the site selection of offshore wind farms. Criteria include technical cost, social and environmental aspects. Determined priorities and preferences of relevant experts for siting criteria. It has been discovered that some criteria are uncritical for OWF site selection. Interval-valued fuzzy-rough numbers based Delphi method is proposed to reflect uncertainty of inaccurate and vague information.